Research Profile of Problem Based Learning on Physics Learning During the Covid-19 Pandemic - Binar Kurnia Prahani; Budi Jatmiko; Tan Amelia; Nova Allysa Qotrunnada; Shalsa Billa Ardhana Neswary; Kirana Aureola Arzak (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
This study was conducted with the aim of analyzing the profile of the Problem Based Learning Model in Physics learning during the Covid-19 Pandemic. The research method used is literature study or literature study. The data collection technique used is to look for relevant journals that will be used as references, The journals analyzed were 32 journals, most of which were reputable international journals and journals published in the range of 2020-2022, because at that time the Covid-19 pandemic occurred in Indonesia. From the results of research that has been carried out learning physics during this pandemic has quite an impact on student learning outcomes. In physics lessons, many students experience misconceptions, do not understand physics concepts and their enthusiasm for learning decreases. One model that may be relevant during the COVID-19 pandemic is the model discussed in this study, namely Problem Based Learning. It is proven that the Problem Based Learning model in physics learning during the covid-19 pandemic in Indonesia is effectively used in improving students' problem solving abilities, critical thinking, creative thinking, and student argumentation. Even though there are some obstacles such as the uneven internet in Indonesia which prevents them from accessing the materials. And also still need relevant teaching materials and learning tools during the covid-19 pandemic.